Data Security Governance Practices under the Background of AI Era - Na, Guisheng (Journal of Theory and Practice of Engineering Science, 2025)
As the world enters the “digital economy,” big data has become the most significant production factor, and various big data application environments pose new demands on data security. Consequently, ensuring data security has become a topic of concern in numerous industries. This article aims to analyze the practice of data security governance and hopes to provide some assistance to relevant personnel.